Role of Microglia and Astrocytes in Spinal Cord Injury Induced Neuropathic Pain. Issue 3 (July 2021) - Miranpuri, Gurwattan S.; Bali, Parul; Nguyen, Justyn; Kim, Jason J; Modgil, Shweta; Mehra, Priya; Buttar, Seah; Brown, Greta; Yutuc, Noemi; Singh, Harpreet; Wood, Aleksandar; Singh, Jagtar; et al.
Background: Spinal cord injuries incite varying degrees of symptoms in patients, ranging from weakness and incoordination to paralysis. Common amongst spinal cord injury (SCI) patients, neuropathic pain (NP) is a debilitating medical condition. Unfortunately, there remain many clinical impediments in treating NP because there is a lack of understanding regarding the mechanisms behind SCI-induced NP (SCINP). Given that more than 450, 000 people in the United States alone suffer from SCI, it is unsatisfactory that current treatments yield poor results in alleviating and treating NP. Summary: In this review, we briefly discussed the models of SCINP along with the mechanisms of NP progression. Further, current treatment modalities are herein explored for SCINP involving pharmacological interventions targeting glia cells and astrocytes. Key message: The studies presented in this review provide insight for new directions regarding SCINP alleviation. Given the severity and incapacitating effects of SCINP, it is imperative to study the pathways involved and find new therapeutic targets in coordination with stem cell research, and to develop a new gold-standard in SCINP treatment.